Legal Protection For Vulnerable Community Groups Due To Limited Digital Access (Open Society Conference, 2025)
Digital transformation brings significant changes in various aspects of life, including education, health, economy, and public services. However, this development is not yet fully inclusive. The limited availability of digital infrastructure in certain regions has created access gaps, especially for vulnerable groups such as communities in 3T areas (frontier, outermost, and least developed), persons with disabilities, and the elderly. This research aims to analyze the existing forms of legal protection, identify implementation barriers, and offer a legal framework model that can guaranty equal rights in accessing digital technology. This research uses a normative juridical method with a statutory approach, conceptual approach, and comparative approach. The research results show that existing regulations, although they have addressed the right to access information and digital-based public services, have not fully provided effective protection for vulnerable groups due to a lack of regulatory integration, limited infrastructure, and low digital literacy. And the ideal model of a legal framework to ensure equality in accessing digital technology is a model that recognizes the right to digital access as a constitutional right and part of human rights, includes affirmative regulations that promote substantive equality, and is equipped with institutional instruments and inclusive oversight mechanisms. Without such a comprehensive legal framework, digital transformation has the potential to deepen social inequalities, rather than reduce them.